2013
DOI: 10.2500/ajra.2013.27.3921
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Mometasone Furoate and Desloratadine in Obstructive Sleep Apnea Syndrome Patients with Allergic Rhinitis

Abstract: Nasal obstruction due to nasal congestion causes increases in airway resistance and can lead to development of OSAS. We concluded that treating AR with Ns has both positive effects on OSAS and daily activity. However, adding Ah to this treatment did not show improved effects compared with placebo treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…Several nasal decongestants have been trialed for OSA severity. The effect on AHI of mometasone alone and in combination with the antihistaminic desloratadine was measured in patients with allergic rhinitis by Acar et al [42] in a four-arm (mometasone, desloratadine, mometasone + desloratadine and placebo) trial with 80 patients. While desloratadine alone or in combination with mometasone did not show significant improvement of OSA severity, mometasone alone did, with a reduction in AHI by 17% compared to placebo.…”
Section: Upper Airway Anatomymentioning
confidence: 99%
“…Several nasal decongestants have been trialed for OSA severity. The effect on AHI of mometasone alone and in combination with the antihistaminic desloratadine was measured in patients with allergic rhinitis by Acar et al [42] in a four-arm (mometasone, desloratadine, mometasone + desloratadine and placebo) trial with 80 patients. While desloratadine alone or in combination with mometasone did not show significant improvement of OSA severity, mometasone alone did, with a reduction in AHI by 17% compared to placebo.…”
Section: Upper Airway Anatomymentioning
confidence: 99%
“…[46] Two recent studies evaluated the effects of allergic rhinitis treatment for OSA, and both found significant improvements in OSA symptomatology. [47, 48] Underlying mechanisms of the improvement were thought to be related to improvements in nasal inflammation with a resultant decreased nasal obstruction. Although the mean age of the participants in these studies was approximately 49 years, the results may also be applicable to older adults – though again, further studies are needed.…”
Section: Special Considerations In Older Adultsmentioning
confidence: 99%
“…The primary outcome of interest, reported in all 8 studies in our systematic review, was AHI, providing posttreatment data for a total of 228 patients. [22][23][24][25][26][31][32][33] Three of these studies evaluated nasal steroids 24,31,32 and, of these, 2 were placebo-controlled. 24,32 Qualitatively, all nasal steroid studies showed statistically significant improvement in AHI compared with pretreatment or placebo.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies showed a 1-to 4-point reduction in ESS scores with TNTs, 23,31-33 2 of which demonstrated a statistically significant improvement. 31,32 According to Patel et al, the minimum clinically important difference (MCID) for ESS scores in adult OSA patients who were treated with CPAP was approximately −2.65. Of the studies we reviewed, only 1 demonstrated a clinically significant improvement in ESS greater than the MCID.…”
Section: Subjective Outcomes Of Topical Nasal Treatment For Osamentioning
confidence: 99%